TO INCREASE THE INTEREST OF ELEMENTARY SCHOOL STUDENTS IN SPORTS AND TO MAKE THEM REGULARLY ENGAGE IN SPORTS - Achilov, Oybek Hakimovich (Educational Research in Universal Sciences, 2023)
This article provides information about the legal basis for the development of sports in the Republic of Uzbekistan, the reforms in the field of physical education and sports in our country, and the positive aspects of organizing physical education lessons and competitions among schoolchildren.